FENOMENOLOGIS SAINS BERBASIS SPIRITUALITAS DALAM KAJIAN AL-QUR’AN - Zamakhsyari Abdul Majid (STIQ al-Lathifiyyah Palembang, 2018)
This paper shows the success of Al-Quran as a representation of scientific change of science that is very basic and deep. Phenomenological science in human life experienced a very rapid and comprehensive civilization. This will be balanced by improving the structure of human thinking in seeing and living a global life as it is today. The Qur'an provides knowledge of the principles of science and education, which are always associated with metaphysical knowledge, morality and spirituality. This study also intends to address the evidence of integrated science education in the perspective of the Qur'an. As well as trying to maximize the education of mod-ern science with knowledge of spirituality based on the study of Al-Qur'an Sciences in human life. This phenomenon brings the paradigm to humans, in the view of science, which makes the basis of knowledge assumption begins from the intellect (human intellect) in understanding the phe-nomenon that occurs